Evaluación in vitro del efecto pulguicida de los extractos obtenidos a partir de la altamisa (Ambrosia arborescens mill) en pulgas de un refugio canino de la ciudad de Popayán – Cauca (2022)
This research was initiated in order to replace the use of external chemical parasiticides, formulating different concentrations from the mugwort (Ambrosia arborescens mill) on the flea (Ctenocephalides spp). The plant material was collected in the village of La Betania in the municipality of Totoró during the first semester of the year 2022, later the plant material is dried and crushed free of moisture and infectious microorganisms. The extraction of plant material was carried out in the Chemistry laboratory of the University of Cauca. This procedure consists of taking 52,680 grams of the ground material which is deposited in the cartridge of the soxhlet equipment, for the extraction 2 L of solvent absolute ethanol was used, which is heated in the flask, condensing the vapors that continuously fall drop by drop on the cartridge containing the sample of soluble analytes. The extraction process was carried out for a week. Once the extract is obtained, the ethanol is eliminated, to obtain it free of ethanol, a process of rotated evaporation of the solvent was used. In this way it is possible to obtain 7,861 grams of ethanolic extract; In short, extraction with the soxhlet equipment has been the method usually used for this type of solid extraction in the different experimental projects. The ectoparasites were collected in the city of Popayán in a canine shelter with different dogs infested with fleas chosen at random through a comb to facilitate handling and discard them in a plastic box; then they are passed in groups according to the concentrations obtained from the mugwort (Ambrosia arborescens mill) corresponding to 25 and 50% arranged in different Petri dishes. Because ethanol was used to dissolve the extract, an initial test was carried out with it to rule out an anomaly with the integrity of the flea and that affects the final results of the work, concluding that there was no condition in these ectoparasites. To evidence the insecticidal effect with respect to the concentrations obtained from mugwort (Ambrosia arborescens mill), 3 Petri dishes were arranged for each group of concentrations at 25 and 50% for a total of 9 boxes. Regarding the methodology, a spray is carried out for each Petri dish labeled, the spray was made on one side to prevent the flea from escaping, from this it is observed every 10 minutes, counting the number of dead and alive fleas; After an hour, a sprinkling is carried out again and the same previous methodology is repeated